The correlation between stress and a type of credit behavior as a characteristic of attitude to money - Mitasova, Elena; Nekrasova, Ekaterina (International Journal of Psychosocial Rehabilitation, 2020)
The article presents the results of the research on the correlation between stress in the life of a person and a type of credit behavior of respondents as a characteristic of their attitude to money. The methodology of "Stress in the life of a person" by Antsupov A.Ya., as well as "Questionnaire of physiological responses to stress", and the author’s questionnaire "Credit behavior" were applied. A new classification of attitude to money based on emotional and behavioral components: positive and negative types of credit behavior; as well as the stress level of a debtor and the debtor’s correlation with the type of credit behavior have been discovered. The differences between stress factors causing a relatively similar stress level in groups with different types of credit behavior have been studied. It has been determined that respondents with a negative type of credit behavior possess psychosomatic symptoms of life stress in contrast to respondents with a positive credit behavior, which indicates the correlation between stress and a type of credit behavior, and confirms the hypothesis proposed in the study. Psychotherapeutic objectives of psychological counseling for debtors with different types of credit behavior have been revealed: for a negative type, the attention should be paid to the intrapersonal conflict, as well as to refocusing on the future and to the search for financial resources, while for a positive credit behavior the concentration should be on reduction of work-related stress. "A checklist for borrowers" has been developed. The results obtained would allow to conduct a deeper analysis of credit behavior as well as to provide more effective psychological counselling to the debtors.